Sustainable Financial Literacy: Lessons from Traditional Practices - Romi Kurniadi; Nurmala Sari; Novia Sri Dwijayanti (Yayasan Keluarga Guru Mandiri, 2025)
The study investigates the role of indigenous knowledge in shaping green financial literacy within households residing near the Batang Hari River, Jambi, Indonesia, addressing the gap between traditional practices and modern sustainability goals. Employing a qualitative ethnographic approach, the research investigates how traditional values such as frugality, resource sharing, and sustainable asset management are embedded in household financial practices. The findings reveal that families prioritize saving, invest in eco-friendly technologies, and adopt sustainable consumption patterns, such as reducing plastic use and utilizing organic fertilizers. These practices enhance both financial resilience and environmental sustainability. A key contribution of this study is its innovative approach to combining local wisdom with modern green finance principles, offering a culturally relevant framework for financial literacy. The intergenerational transmission of these values ensures long-term sustainability, emphasizing the role of families in promoting eco-conscious financial behaviors. This research provides valuable insights for policymakers and educators to design green financial education programs rooted in local culture, ensuring broader accessibility and impact. By bridging traditional knowledge with contemporary sustainability goals, this study contributes to developing a unique framework for fostering financial and environmental resilience in communities facing economic and ecological challenges.